Determination of Sodium and Copper in Ohasari Sea Shell By Radiochemical Neutron Activation Analysis - Sudi Ariyanto (BATAN, 2001)
ABSTRACT Elemental analysis of Sodium and Copper in Ohasari sea shell has been performed by radiochemical NAA. The concentration of Na in Ohasari shell is found to be 4745.00 ± 119.29 ppm. The concentration of Cu in Ohasari shell is found to be 17.29 ± 1.76 ppm. Ohasari shell contains some elements such as Ta-182, Pt-197, I-131, I-132, I-133, Ce-144, Ce-141, Sc-47, Te-132, Hg-203, Au-198, Ru-103, Cu-64, As-74, As-76, Sb-122, Na-24. ABSTRAK Telah dilakukan pengukuran Sodium dan Tembaga dalam kulit kerang jenis Ohasari dengan menggunakan NAA dan radiokimia. Ditemukan bahwa konsentrasi Na dalam kerang 4745.00 ± 119.29 ppm, sedangkan konsentrasi Cu 17.29 ± 1.76 ppm. Beberapa unsur yang terkandung di dalam kulit kerang Ohasari adalah Ta-182, Pt-197, I-131, I-132, I-133, Ce-144, Ce-141, Sc-47, Te-132, Hg-203, Au-198, Ru-103, Cu-64, As-74, As-76, Sb-l22, Na-24.